Use of sunbeds by minors despite a legal regulation: Extent, characteristics, and reasons - Diehl, Katharina; Bock, Christina; Greinert, Rüdiger; Breitbart, Eckhard W.; Schneider, Sven (Journal of Public Health, 2013)
Aim: Sunbed use can have severe health consequences, e.g. skin cancer, especially for children and adolescents. Therefore, our aim was to quantify how many adolescents use tanning beds despite a legal ban in Germany. In addition, we aimed at identifying characteristics of users and at analyzing reasons for use and user behavior. Subjects and methods: The nationwide representative SUN-Study 2012 included a subgroup of 518 minors (14-17 years). Besides calculating the prevalence, we used bivariate statistics to identify user groups and to compare minors with adults in terms of reasons for use, place of last use, and obtained advisory service. Results: Overall, 8.7 % of minors had ever used a sunbed; 5.2 % used it during the last 12 months. Out of these, nearly a half was not aware of the legal ban for minors. Users were mainly smokers, had darker skin, and a migration background. Compared to adults, minors were more likely to use unsupervised sunbeds and were less frequently advised by service personnel. Conclusion: The data showed that minors use tanning beds, although there is a legal ban in Germany. The circumvention of the ban and the widespread use of unsupervised sunbeds underline the importance of education and further legal requirements. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Adolescent; Germany; Legal aspects; Minors; Sunbed use